“Little poplar burned by the moon”: dendronyms with negative connotations in the lyrics of Anna Akhmatova - Papsheva, G. O.; Golubtsova, N. V.; Matveeva, O. N. (Vestnik of North-Eastern Federal University, 2025)
The article is devoted to the study of the peculiarities of the representation of structures mentioning trees (dendronyms) with negative connotations in the lyrics of Anna Akhmatova. The author’s individual model of perception of the plant world is reconstructed, the image of a tree as a mediator is recreated, making a connection between the “living” and “dead”, the “upper” and “lower” world. The complexes of negative connotations interpreting the traditional meanings of dendronyms in the context of individual author’s perception, taking into account the frequency of use of certain phytonyms, are determined; the lexical and grammatical specifics of the textual representation of the surrounding world through dendronyms are revealed. The main tools of semantic interpretation of the image of a tree through the systems of “metaphorization of nature” and “psychological landscape” are highlighted. The priorities in the interpretation of the traditional symbolism of trees and shrubs are systematized through a complex of stable themes and motifs: the deformation of a love feeling, reflection after parting, the image of illness as a negative effect of the gap between the human world and the natural world, the image of death, the image of war. The main points of the use of dendronyms are highlighted: psychoemotional, geographical, biographical, existing within the framework of negative evaluative constructions, a classification of floral vocabulary is given, the lexico-semantic group “Trees and shrubs” is considered in detail. The differences in the interpretation and use of various subgroups of dendronyms are systematized: “Wild trees and shrubs”, “Fruit-bearing trees and shrubs”, the thesis of a predominantly urban landscape in the lyrics of Anna Akhmatova is confirmed. It describes the space of a garden, park, manor park and landscape architecture. Conclusions are drawn about the individual author’s model of the artistic world, taking into account the structures containing trees and shrubs in the nomination, the main trends in the functioning of floral vocabulary in the poetic text are highlighted, taking into account the level of metaphorization of phytonyms and the concept of “psychological landscape”, which expressing the feelings and emotions of characters through the name of plants in the fiction text.